Determination of biologically active substances extraction parameters from cranberry leaves - I. K. Vlasova; O. M. Koshovyi; O. S. Kukhtenko; M. A. Komisarenko; Т. V. Ilina; A. M. Kovalyova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The problem of type 2 diabetes due to its prevalence, severity, and complications is one of the most pressing in the world. Plants of the genus Vaccinium are promising sources for the creation of hypoglycemic and hypolipidemic medicines. Studies have shown that the extract from cranberry leaves, obtained with 50 % ethanol solution has prospects to be used for correcting insulin resistance. Therefore, for creating new medicines based on cranberry leaves, it is necessary to determine the optimal parameters of biologically active substances (BAS) extraction from this raw material.